Microbial Communities in Coastal Salt Marshes Along the Southeast Coast of China and their Effects on Carbon Storage - Lv, Chunguang; Li, Yan; Zhang, Huining; Wang, Chenyi; Ren, Min; Zhang, Chiqian (Current Analytical Chemistry, 2025)
<span class=
Keywords: Coastal salt marsh